Trade-off strategies between drought resistance and growth rate of dominant tree species in karst forests within heterogeneous habitats - Jing Wang; Bin Wang; Denghui Wang; Yanping Dong; Jianxing Li; Fang Lu; Wanglan Tao; Yili Guo; Wusheng Xiang; Meilan Wen; Xiankun Li (Scientific Reports)
Abstract This study investigates drought resistance-growth trade-offs in dominant tree species across elevationally stratified habitats (depression, middle slope, hilltop) of Nonggang karst seasonal rainforest in southwestern China. Analysis of 38 species along a 190-meter aridity gradient reveals drought resistance enhancement through foliar modifications: 56.79% increase in cuticle thickness, 56.42% denser palisade mesophyll thickness, and 36.48% expansion in spongy mesophyll thickness, accompanied by 45.67% growth reduction. Structural equation modeling confirms a significant drought resistance-growth trade-off (β = − 0.504), indicating carbon allocation constraints. Hilltop species employ an anisohydric strategy combining stomatal optimization (4.45% shorter length, 27.17% wider apertures achieving 33.10% increased opening) with 15.52% reduced upper epidermis cell width and cuticle thickening, enhancing hydraulic efficiency despite 111.63% elevated dark respiration rates. This high-resistance/low-growth strategy contrasts with depression-adapted species showing superior low-light performance: 30.35% higher quantum yield and 63.44% lower light compensation points compared to hilltop counterparts. Environmental driver analysis identifies soil moisture (β = − 0.706) and bedrock exposure (β = − 0.594) as key factors shaping trait divergence. Drought suppresses growth through dual pathways: direct resource limitation (β = − 0.667) and indirect metabolic costs of resistance traits (β = − 0.469). Coordinated leaf trait evolution reduces niche overlap via drought-growth trade-offs, establishing habitat filtration-mediated biodiversity maintenance in karst ecosystems. These results provide a multidimensional framework for balancing stress resistance and productivity in tropical karst vegetation restoration.